Collateral damage [compact disc, unabridged] - Jance, Judith A. (Jance, Judith A. Ali Reynolds novel., 2023)
After twenty years behind bars, a disgraced former cop is out on parole and focused on just one thing: revenge. Now Ali Reynolds and High Noon Enterprises must face the dangerous consequences.